2016
DOI: 10.1007/s00401-016-1582-9
|View full text |Cite
|
Sign up to set email alerts
|

Human-to-mouse prion-like propagation of mutant huntingtin protein

Abstract: Huntington’s disease (HD) is an autosomal dominant neurodegenerative disorder of the central nervous system (CNS) that is defined by a CAG expansion in exon 1 of the huntingtin gene leading to the production of mutant huntingtin (mHtt). To date, the disease pathophysiology has been thought to be primarily driven by cell-autonomous mechanisms, but, here, we demonstrate that fibroblasts derived from HD patients carrying either 72, 143 and 180 CAG repeats as well as induced pluripotent stem cells (iPSCs) also cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
128
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(145 citation statements)
references
References 48 publications
(85 reference statements)
7
128
1
Order By: Relevance
“…Later, the formation of aggregates was evaluated using the same cells (HD72-iPSC-derived neural precursors) a short time after transplantation, and no evidence of aggregates was found in the mouse transgenic model. Recently, Jeon et al [119] performed more studies and confirmed that the mutant HTT protein derived from NPCs generated from iPSC-HD is able to proliferate in vivo in fetal host tissue. They associated this effect to the activity of exosomes, since it has been demonstrated in vivo and in vitro that exosomes can transport mutant Htt.…”
Section: Limitations On Neuronal Cells Derived From Pluripotent Stem mentioning
confidence: 92%
See 2 more Smart Citations
“…Later, the formation of aggregates was evaluated using the same cells (HD72-iPSC-derived neural precursors) a short time after transplantation, and no evidence of aggregates was found in the mouse transgenic model. Recently, Jeon et al [119] performed more studies and confirmed that the mutant HTT protein derived from NPCs generated from iPSC-HD is able to proliferate in vivo in fetal host tissue. They associated this effect to the activity of exosomes, since it has been demonstrated in vivo and in vitro that exosomes can transport mutant Htt.…”
Section: Limitations On Neuronal Cells Derived From Pluripotent Stem mentioning
confidence: 92%
“…However, more recent publications suggested that the pathology does not occur purely at the cellular level. Observation of aggregates of mutant HTT within fetal striatal allografts in patients with HD provides strong evidence for the existence of a non-cell-autonomous mechanism of action, which accounts for the HTT protein to spread via pathological cell-cell communication [119,121].…”
Section: Limitations On Neuronal Cells Derived From Pluripotent Stem mentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is supported by the markedly reduced risk of sporadic PD in patients undergoing vagotomy [26], and the ability of fibrillar alpha-synuclein to travel from the gut to the brainstem of experimental animals [27]. Similar prion like spreading has been proposed in HD -transplantation of human HD fibroblasts into the ventricles of wild-type animals results in the formation of mutant Huntingtin aggregates in wild-type cells [28]. In short, peripheral silencing of neurodegenerative disease proteins has the potential to impact disease progression.…”
Section: Introductionmentioning
confidence: 87%
“…However, mHTT is not always found inside cellular compartments, but is also present outside the cell boundary, notably in the cerebrospinal fluid, plasma, and extracellular matrix. [2][3][4][5][6] The HD gene product is further expressed outside the CNS, leading to peripheral pathology. 7,8 In theory, mHTT aggregates should be found in every tissue and cell type of the body, but their presence/ location within the spinal cord and their pathological significance at this site have not been investigated, and this includes effects on the blood-spinal cord barrier (BSCB).…”
mentioning
confidence: 99%